Mastering OpenCV Android application programming : master the art of implementing computer vision algorithms on Android platforms to build robust and efficient applications /: master the art of implementing computer vision algorithms on Android platforms to build robust and efficient applications. (2015) - Kapur, Salil; Thakkar, Nisarg
No abstract available